2019
DOI: 10.1093/nop/npz048
|View full text |Cite
|
Sign up to set email alerts
|

Interval between planning and frameless stereotactic radiosurgery for brain metastases: are our margins still accurate?

Abstract: Background Advances in intracranial stereotactic radiosurgery (SRS) have led to dramatically reduced planning target volume (PTV) margins. However, tumor growth between planning and treatment may lead to treatment failure. Our purpose was to assess the kinetics of tumor growth before SRS for brain metastases. Methods This retrospective, monocentric study included all consecutive patients (pts) treated for brain metastases sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Our study of large brain metastases showed that tumor volume increases in a short period of time. This finding is similar to those in previous reports measuring brain metastases of various sizes in non-small cell lung cancer and melanoma, which showed that tumor progression between dMRI and pMRI was observed in 82% of cases [ 7 ]. However, our average growth rate of 0.21 cm 3 /day appears to be considerably higher than previously reported rates.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study of large brain metastases showed that tumor volume increases in a short period of time. This finding is similar to those in previous reports measuring brain metastases of various sizes in non-small cell lung cancer and melanoma, which showed that tumor progression between dMRI and pMRI was observed in 82% of cases [ 7 ]. However, our average growth rate of 0.21 cm 3 /day appears to be considerably higher than previously reported rates.…”
Section: Discussionsupporting
confidence: 92%
“…If the tumor grows beyond the PTV margin between SRS-planning magnetic resonance imaging (MRI) and delivery of treatment, the tumor may not receive an adequate radiation dose. Although previous studies have reported growth rates of small brain metastases before sfSRS planning [ 7 9 ], to the best of our knowledge, none have examined tumor growth speed of large (≥ 2 cm) brain metastases before fSRS planning. Therefore, we aimed to examine the growth speed of large brain metastases between diagnostic and radiosurgical planning MRI and investigate the predictors of rapid tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have wondered whether the interval between SRS planning and treatment is accurate [37][38][39][40]. In order to study this, they compared volumes from diagnostic imaging and radiosurgery planning MRI and extrapolated the growth linearly to the day of SRS, since only two time points were available.…”
Section: Discussionmentioning
confidence: 99%
“…With precise delineation and tight PTV margins, delays from the treatment planning to the treatment completion must be as short as possible. A recent brain MRI (<15 days) is essential for the delineation of GTV and it often needs to be renewed to meet this criterion [ 44 ]. With our workflow, one patient could be treated within one week of the diagnostic MRI (vs 3 to 4 weeks).…”
Section: Discussionmentioning
confidence: 99%